Korelasi Antara Jenis Kelamin dan Umur Terhadap Performan Domba Persilangan Lokal Dengan Hairsheef - Helmi M. Yahya (Agricultural Faculty, 2002)
ABSTRACT.The research to study the effect of correlation between male and female local cross goat with hairsheep to performance. The parameters were body weight, body length, sholder height, heart girth and chest of heart girth. Result of the research shows that there were very significant between age and all prameters cros goats above. The regretion of body weight with age, body length with age, shoulder height with age, heart girth with age and chest of heart girth with age to crossing local goats and male hairsheep were = 2.07 + 0.62 X, = 18,58 + 1.50 X, = 32.97 + 0.84 X, = 31.49 + 1,50 X, and = 13.98 + 0.51 X, respectively. The following regretion of female goats to body weight with age, body length with age, shoulder height with age, heart girth with age and chest of heart girth with age were = 2.10 + 0.50 X, = 17.96 + 1.53 X, = 32.06 + 0.81 X, = 30.69 + 1.51 X and = 13.27 + 0.34 X, respectively.